PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE PADA ELEMEN ALAT UKUR DAN PENGUKURAN BIDANG TJKT DI SMKN 1 SOLOK SELATAN - Rifki Fuadi; Heri Mulyono; Haris Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the need for effective learning media to support students' understanding of the abstract technical material in the Basics of Computer Network Engineering and Telecommunications, particularly regarding the Measuring Instruments and Measurement element. This problem often arises when learning is conducted only through conventional methods, limiting student engagement and understanding. The objective of this research was to produce a valid and practical website-based learning media for the Measuring Instruments and Measurement element in the field of Computer Network Engineering (TJKT) at SMK Negeri Solok Selatan. Development was conducted using the Research and Development (R&D) method using the System Development Life Cycle (SDLC) model with an iterative approach. The stages included needs analysis, design, development, testing, and implementation. The research instruments included questionnaires assessing website validity, content validity, and teacher and student practicality. The research subjects consisted of 3 lecturers (2 website validators, 1 content validator), 3 teachers (1 content validator, 2 users), and 29 10th-grade students of TJKT 2 SMKN 1 Solok Selatan. Data collection techniques were conducted through a prepared questionnaire, and data analysis techniques used a Likert scale. The validation results by the system expert obtained a score of 85.24% and by the material expert 93.75%, both of which are categorized as very feasible. The practicality test obtained a score of 92.71% from teachers and 91.72% from students, both of which are categorized as very practical. These findings indicate that the developed learning media is able to help students understand technical concepts independently and support teachers in delivering material systematically and interestingly.